Arabidopsis RhoGDIs Are Critical for Cellular Homeostasis of Pollen Tubes . Issue 2 (11th December 2015) - Feng, Qiang-Nan; Kang, Hui; Song, Shi-Jian; Ge, Fu-Rong; Zhang, Yu-Ling; Li, En; Li, Sha; Zhang, Yan
Abstract : In planta GDIs for ROP GTPases support pollen germination and tube growth. Abstract: Rhos of plants (ROP s) play a key role in plant cell morphogenesis, especially in tip-growing pollen tubes and root hairs, by regulating an array of intracellular activities such as dynamic polymerization of actin microfilaments. ROP s are regulated by guanine nucleotide exchange factors (RopGEFs), GTPase activating proteins (RopGAPs), and guanine nucleotide dissociation inhibitors (RhoGDIs). RopGEFs and RopGAPs play evolutionarily conserved function in ROP signaling. By contrast, although plant RhoGDIs regulate the membrane extraction and cytoplasmic sequestration of ROP s, less clear are their positive roles in ROP signaling as do their yeast and metazoan counterparts. We report here that functional loss of all three Arabidopsis ( Arabidopsis thaliana ) GDI s ( tri - gdi ) significantly reduced male transmission due to impaired pollen tube growth in vitro and in vivo. We demonstrate that ROP s were ectopically activated at the lateral plasma membrane of the tri - gdi pollen tubes. However, total ROP s were reduced posttranslationally in the tri - gdi mutant, resulting in overall dampened ROP signaling. Indeed, a ROP5 mutant that was unable to interact with GDIs failed to induce growth, indicating the importance of the ROP -GDI interaction for ROP signaling. Functional loss of GDI s impaired cellular homeostasis, resulting in excess apical accumulation of wall components in pollen tubes, similar to that resulting from ectopic phosphatidylinositol 4, 5-bisphosphate signaling. GDIs and phosphatidylinositol 4, 5-bisphosphate may antagonistically coordinate to maintain cellular homeostasis during pollen tube growth. Our results thus demonstrate a more complex role of GDIs in ROP -mediated pollen tube growth.